A Biomimetic Biphasic Scaffold Consisting of Decellularized Cartilage and Decalcified Bone Matrixes for Osteochondral Defect Repair - Cao, Runfeng; Zhan, Anqi; Ci, Zheng; Wang, Cheng; She, Yunlang; Xu, Yong; Xiao, Kaiyan; Xia, Huitang; Shen, Li; Meng, Depeng; Chen, Chang (Frontiers in Cell and Developmental Biology, 2021)
It is challenging to develop a biphasic scaffold with biomimetic compositional, structural, and functional properties to achieve concurrent regeneration of both superficial cartilage and superficial subchondral bone in osteochondral defects (OCDs). This study developed a biomimetic biphasic scaffold for OCD repair by an ‘‘iterative layering’’ freeze-drying technique that controlled the composition, pore size, and substrate stiffness in each phase of the scaffold. The biphasic scaffold consisted of a superficial decellularized cartilage matrix (DCM) and underlying decalcified bone matrix (DBM) with distinct but seamlessly integrated phases that mimicked the structure and composition of osteochondral tissue, in which the DCM phase had relative low stiffness and small pores (approximately 134 μm) and the DBM phase had relative higher stiffness and larger pores (approximately 336 μm). In vitro results indicated that the biphasic scaffold was biocompatible for bone morrow stem cell (BMSC) adhesion and proliferation, and the superficial DCM phase promoted chondrogenic differentiation of BMSCs, whereas the DBM phase was inducive for osteogenic differentiation of BMSCs. Furthermore, compared with the untreated control group, the biphasic scaffold significantly enhanced concurrent regeneration of superficial cartilage and underlying subchondral bone in a rabbit OCD model. Our results demonstrate that the biomimetic biphasic scaffold has a good osteochondral repair effect.